Comparing the Environmental Footprint of Web Stacks in the RealWorld Apps - Guimarães, Allysson; Andrade, Rodrigo (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2025: Anais do XIX Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2025)
As concerns about the environmental impact of software continue to grow, recent studies have explored how software consumes energy and emits greenhouse gases, often using isolated benchmarks or specific tasks. However, the environmental implications of implementing the same application across different technology stacks remain underexplored. In this paper, we investigate the energy consumption, execution time, and carbon dioxide emissions of a benchmark web application implemented using three distinct technology stacks. Through 32 usage scenarios and the analysis of 10 efficiency-related metrics, our results reveal no statistically significant differences among the stacks regarding their environmental footprint. These findings suggest that replacing the entire technology stack may not be as impactful as optimizing specific application functionalities when aiming for more sustainable software.